2016
DOI: 10.1371/journal.pone.0153770
|View full text |Cite
|
Sign up to set email alerts
|

Daboxin P, a Major Phospholipase A2 Enzyme from the Indian Daboia russelii russelii Venom Targets Factor X and Factor Xa for Its Anticoagulant Activity

Abstract: In the present study a major protein has been purified from the venom of Indian Daboia russelii russelii using gel filtration, ion exchange and Rp-HPLC techniques. The purified protein, named daboxin P accounts for ~24% of the total protein of the crude venom and has a molecular mass of 13.597 kDa. It exhibits strong anticoagulant and phospholipase A2 activity but is devoid of any cytotoxic effect on the tested normal or cancerous cell lines. Its primary structure was deduced by N-terminal sequencing and chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 64 publications
(63 reference statements)
2
17
0
Order By: Relevance
“…Aside from the prothrombinase complex, we also evaluated the modulation of both intrinsic and extrinsic tenase complexes by CTX, and observed that the toxin inhibited both pathways. Previous reports of this nature have also been published for other svPLA 2 s such as daboxin P, from Daboia russelii snake venom, and 3-finger toxins such as exactin, from Hemachatus haemachatus venom, in which both toxins inhibit extrinsic and intrinsic tenase complexes [33,34]. Moreover, our data shows that CTX is more efficient in inhibiting the intrinsic tenase complex than the extrinsic, similarly to that observed for daboxin P and exactin.…”
Section: Discussionsupporting
confidence: 86%
“…Aside from the prothrombinase complex, we also evaluated the modulation of both intrinsic and extrinsic tenase complexes by CTX, and observed that the toxin inhibited both pathways. Previous reports of this nature have also been published for other svPLA 2 s such as daboxin P, from Daboia russelii snake venom, and 3-finger toxins such as exactin, from Hemachatus haemachatus venom, in which both toxins inhibit extrinsic and intrinsic tenase complexes [33,34]. Moreover, our data shows that CTX is more efficient in inhibiting the intrinsic tenase complex than the extrinsic, similarly to that observed for daboxin P and exactin.…”
Section: Discussionsupporting
confidence: 86%
“…Alkylation of histidine residue of Rv(i) PLA 2 was carried out using p ‐bromophenacyl bromide (pBpB) . Briefly, 150 μg of Rv(i) PLA 2 was incubated with 30 μg of pBpB (dissolved in 100% ethanol) for 20 h. The same amount of the purified protein in 100% ethanol was considered as the vehicle control.…”
Section: Methodsmentioning
confidence: 99%
“…Snake venom PLA 2 enzymes play a significant role in inhibiting blood coagulation in envenomated victims. These enzymes interfere with the blood coagulation process either enzymatically by hydrolyzing the phospholipids of platelet membranes and/or nonenzymatically by interacting with the blood clotting factors . In addition to the anticoagulant effect, PLA 2 enzymes also exhibit prominent inflammatory responses in victims both locally and systematically .…”
Section: Introductionmentioning
confidence: 99%
“…Coagulation assays were done using platelet‐poor plasma (PPP) prepared from citrated goat blood by centrifugation at 3000 rpm for 20 min at 16°C . A control was run in parallel in each assay where only buffer (20 mM Tris‐Cl, pH 7.4) was used and normal plasma clotting time was recorded using a coagulation analyzer (Tulip Diagnostics, Alto Santa Cruz, Goa, India).…”
Section: Methodsmentioning
confidence: 99%